VD_FINDINFO Arrêt / 2012 / 625 vom 23. August 2012 - VD Tribunal cantonal (2012)
PRIME D'ASSURANCE-MALADIE, PRESTATION D'ASSISTANCE, REVENU DÉTERMINANT | 16 LAMal, 65 LAMal, 24 LI, 37 LI, 11 LVLAMal, 12 LVLAMal, 9 LVLAMal, 17 RLVLAMal, 21 RLVLAMal, 23 al. 2 let. e RLVLAMal